Knowledge Management in R&D Centres, in the Field of Biomedicine, Using Contemporary Information and Communication Technology and the Methodology of Continuous Improvement - Depta Ryszard (Marketing of Scientific and Research Organizations, 2015)
Some sophisticated medical applications, including advanced therapeutics with monoclonal antibodies, stem cells, and gene therapies are currently available in clinical trials. More revolutionary technologies are coming soon and will be marketed by the best technically advanced companies in the world. R&D companies with a much smaller indicator of technological progress and organizational efficiency, but with a great desire to become a major player in this industry, will also compete for a share of this market.